Racial Disparities in Body Composition of Preterm Infants (P21-049-19) - Jerome, Maggie (Curr Dev Nutr, 2019)
OBJECTIVES: At term-equivalent age, preterm infants have higher % body fat (%BF) than infants born at term. This difference in %BF is often the result of exposure to enriched postnatal diets prescribed to promote rapid weight gain among preterm infants. Because rapid weight gain during infancy and obesity are more prevalent among blacks than among whites, racial disparities in the development of adiposity expressed as %BF need to be explored. The purpose of this study was to compare %BF in two major racial groups using normative data as reference. METHODS: We analyzed data from a prospective study that assessed body composition in preterm infants using air displacement plethysmography (PeaPod®). After stratifying data according to race, we analyzed differences between mean %BF values of preterm infants at the time of hospital discharge and compared these differences to existing references of %BF in preterm infants. A linear regression analysis was performed to account for differences in baseline characteristics. RESULTS: We assessed body composition in 84 preterm infants, of which 47 were black and 37 were white. Mean birthweight was 1471 g and median gestational age was 30 weeks. In preterm infants assessed at the time of hospital discharge, mean %BF was 14.6 ± 3.6 (14.5 ± 2.9 in white infants and 14.6 ± 4.1 in black infants; P = 0.90). The measured %BF at the time of hospital discharge was higher than the expected %BF at equivalent postmenstrual age (mean difference: 4.7 ± 3.5; P < 0.05). After adjustment for BW, GA, sex, and length of hospital stay, this difference between measured and expected %BF was not significantly higher among black infants compared to white infants (5.1 vs. 4.2; P = 0.28). CONCLUSIONS: Black race is not associated with higher %BF at the time of hospital discharge in preterm infants. If racial disparities in body composition exist among former preterm infants, those differences may occur after hospital discharge. Both black and white preterm infants exposed to enriched postnatal diets develop higher than expected %BF by the time of hospital discharge. FUNDING SOURCES: None.